F2 gene G20210A polymorphism and its relationship to plasma hemostasis activity in patients with acute coronary syndromes associated with type 2 diabetes - Karpenko , Olena (The Ukrainian Scientific Medical Youth Journal, 2021)
Complex diseases, such as coronary heart disease and diabetes, are caused by the nonlinear interaction of numerous genetic and environmental risk factors. Characterization not only of candidate genes but also of complex interactions between them is obviously a more powerful approach to the study of such diseases. The inconsistency of data from various studies is explained by the fact that the genetic risk of coronary heart disease is not based on the action of a single gene, but on the interaction between several pathophysiological pathways controlled by several genes and other risk factors. The aim of the study was to determine the state of blood coagulation activity in patients with acute coronary syndrome with concomitant type 2 diabetes mellitus depending on the G20210A polymorphism of the F2 gene. Materials and methods: In the course of the study we examined 60 patients treated in the Department of Emergency Cardiology: 30 patients with acute coronary syndrome, 30 patients with acute coronary syndrome in combination with type 2 diabetes and 15 healthy individuals (control group). For molecular genetic analysis, DNA samples of patients isolated from venous blood by sorbent method were used. The G20210A polymorphism of the F2 gene was determined by the polymerase chain reaction using a two-primer system and ready-made reagents (Sintol, Russia) on an Applied Biosystems 7500. Statistical processing of the results was performed using SPSS-23. Results: After analyzing the data, we can conclude that the general trend of changes in plasma hemostasis in the group of patients with acute coronary syndrome intensified coagulation processes, but they did not depend on mutations in the F2 gene. Conclusions: Thus, in the group of patients with acute coronary syndrome, no significant relationship was found between coagulation parameters, anticoagulant system and G20210A polymorphisms.